Tantangan Dan Peluang Jaringan 5G Dalam Meningkatkan Operasional Perusahaan - Mesya Nandawani Manik; Rayyan Firdaus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
5G (5th Generation) networks are a major breakthrough in the world of wireless communication technology that offers much faster data transfer rates, very low latency, and greater capacity compared to previous generations. The development of 5G networks brings both challenges and opportunities for enterprises in improving their operations. The main challenges include large infrastructure investments, limited frequency spectrum, data security and privacy, and compatibility and interoperability with existing technologies. On the other hand, the opportunities offered by 5G networks include better connectivity for the Internet of Things (IoT), real-time communication with low latency, real-time analysis of big data, virtual and augmented reality applications, and the development of innovative new services and business models. To capitalise on these opportunities, companies need to invest in 5G technology, develop the right digital strategy, pay attention to data security and privacy aspects, and collaborate with relevant parties. By facing the challenges and properly utilising the opportunities of 5G networks, companies can achieve a competitive advantage and drive sustainable business growth in this increasingly digital era. This research adopts a systematic literature review (SLR) approach to investigate and analyze literature relevant to corporate business transformation.